Contribution of Chinese and Indian tourism to Australia: A comparative econometric study - Vu , Jo; Hoa, Tran Van (Archives of Business Research, 2020)
Under the current widespread economic integration of new international trade theory, the world’s two most populous countries, China and India, have achieved high growth, reducing poverty, increasing income and living standards and, as a result, provided good sources of much needed income-generating tourism to international destinations in recent years. The trend in rising tourism including education from China and India to Australia is exponential, and particularly important where the country’s geographical, cultural and educational quality attributes are internationally key attractions. Appropriate studies of this trend and economic outcomes, with robust and reliable empirical findings for credible analysis have been inadequate to date. The project addresses this gap by proposing to investigate the economic contributions of China and India’s tourism to Australia, and their determination for strategic international policy analysis. Significantly, this is done from an economic integration framework, which is also the expenditure (as opposed to production or income) perspective of the United Nations System of National Accounts 1993/2008. A multi-simultaneous equation model of endogenous Australian growth and Chinese and Indian tourism determination is developed. The model novelly incorporates gravity theory and classical consumer demand contributors, Ironmonger-Lancaster commodity attributes and Johansen policy impact add-and sub-factors explicitly in the economic integration framework, and is estimated by system methods with official economic and tourism 1992-2016 data. The findings will provide appropriate and much needed evidence-based inputs on the major economic integration contributors to Australia’s growth, Chinese and Indian tourism causality to key stake-holders such as tourism policy-makers, analysts and operators for international strategic policy analysis and practical implementation.